THE IMPORTANCE OF CYTOKINES IN PATIENTS WITH CIRRHOSIS OF THE LIVER OF VIRAL ETIOLOGY. (CAHIERS MAGELLANES-NS, 2024)
. Liver cirrhosis is currently a pressing medical problem and is considered the terminal stage of all chronic liver diseases. According to the World Health Organization, about two million people die from liver disease every year. Liver disease accounts for 4% of all deaths worldwide, meaning 1 in 25 deaths is due to this disease. In many cases, the etiological factor of acute hepatitis is hepatotropic viruses [1]. In recent years, in our region there has been a significant increase in liver cirrhosis due to viral hepatitis.Objective: study of serum concentration of pro- (IL-17A) and anti-inflammatory (IL-10) mediators of immune response in CPU. Material and methods: Serum of 72 patients with CPU. The control group consisted of 28 practically healthy persons of similar age. Serum IL-17A concentration was determined by solid-phase enzyme immunoassay using CYTOKINE CJSC test systems (Russia, Saint Petersburg). Results: Results suggest that IL-17A and IL-10 overexpression are strongly associated with the progression of chronic HBV and HCV infection and therefore severe liver cirrhosis